2020
DOI: 10.9770/jesi.2020.7.4(28)
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment, HRM practices and organizational performance: a case study of Jordanian commercial banks

Abstract: This study aimed to identify the role of empowerment and Human Resource Management (HRM) practices on Organizational Performance (OP) amongst 13 Jordanian commercial banks. The research adopted a descriptive and analytical approach to highlight the concepts of the study, and analyzed and extracted the results through a random sample of 180 managers and vice-managers. To achieve the objectives of the study a questionnaire was developed to gather the optimum information from the study sample, and based on that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
0
17
0
2
Order By: Relevance
“…Organizations also provide opportunities for their representatives to participate in the advancement of organizational objectives and approach progress, then empower them to create unapplied thinking that is the basis of organizational implementation. Although there has been extensive writing on HRM practices and innovation performance, analysts have ultimately sought to combine these two queries on flow (Alkhazali et al, 2020). The following areas offer some assumptions about the influence of encouraging communication and data trade between AMO practices and sustainable development for SMEs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations also provide opportunities for their representatives to participate in the advancement of organizational objectives and approach progress, then empower them to create unapplied thinking that is the basis of organizational implementation. Although there has been extensive writing on HRM practices and innovation performance, analysts have ultimately sought to combine these two queries on flow (Alkhazali et al, 2020). The following areas offer some assumptions about the influence of encouraging communication and data trade between AMO practices and sustainable development for SMEs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A number of people think they have examined this relationship in an Asian setting. Alkhazali et al (2020) found that HRM practices lead to superior development outcomes, which in turn lead to advanced implementation. Argote et al (2003) highlighted the part of AMO practice and knowledge management in advancing organizational implementation.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Previous study has shown a positive effect of work practices on employee, for example Alkhazali et al, (2020) found positive relationship between empowerment, HRM practices and employee outcomes in Jordanian banks. Similarly, Dayarathna, (2019) examine the impact of HPWS on employees effectiveness in Srilankan's banks and found positive correlation.…”
Section: High-performance Work Practices and Affective Commitmentmentioning
confidence: 86%
“…Studies on entrepreneurial orientation have shown inconsistencies. Majority of the studies conducted on the relationship between entrepreneurial orientation and performance have shown positive impact (Alkhazali et al, 2020). But on the other hand, few researchers contradicted the ndings and highlighted that the relationship between entrepreneurial orientation and performance have insigni cant (Cho & Lee, 2018;Shah & Ahmad, 2019;Hernández-Linares, Kellermanns, López-Fernández, & Sarkar, 2019), or least in uence (Vega-Vázquez, Cossío-Silva, & Revilla-Camacho, 2016; Masa'deh, Al-Henzab, Tarhini, & Obeidat, 2018) or negative (Taheri, Bititci, Gannon, & Cordina, 2019) or curvilinear (Yoon & Solomon, 2017), or inverse U shaped (Luu & Ngo, 2019) relationship.…”
Section: Performance Of Smesmentioning
confidence: 99%